A Four-Station OSTE (Objective Structured Teaching Exercise) in Geriatric Medicine - Don Scott; Sandy Cook; Catherine DuBeau; Paula Podrazik (Association of American Medical Colleges, 2013)
Abstract This module contains all materials needed to conduct and evaluate a four station observed structured teaching exercise (OSTE) in geriatric medicine. The goal of this teaching skills development module is to improve both the teaching of geriatric medicine by non-geriatricians in the in-patient setting and to improve the clinical teaching skills of the participants. Analogous to the observed structured clinical examination, the OSTE is a performance-based teaching assessment using standardized learners and is based on Ericsson's theory of deliberate practice in the development of expertise. This module is designed for the formative assessment of teaching skills in the following geriatric medicine topics: screening for dementia, assessing and managing the delirious patient, proper and improper uses of the Foley catheter, and planning for good transitions of care. Each of these OSTEs occurs in a common clinical teaching setting, either at the bedside, the door-side, or in a team meeting. Participants engage in the deliberate practice of their geriatrics teaching skills by selecting specific geriatric content and teaching skills to practice, receiving structured feedback, and then practicing these tasks again. Each OSTE case is accompanying by a training guide for both simulated learners and simulated patients; a facilitator's guide; assessment and evaluation instruments for the assessment of teaching skills during the OSTE and for the evaluation of the module itself; and tips for conducting the OSTE.